2013
DOI: 10.1029/2012ja017861
|View full text |Cite
|
Sign up to set email alerts
|

Pc1–2 auroral pulsations

Abstract: [1] By observations at Lovozero station (64.3 N, 114.3 E CGM coordinates), we have investigated two events of auroral pulsations of Pc1-2 type with periods in the range 2.5-7 s accompanied by similar geomagnetic pulsations. Luminous variations in different parts of the sky were found by photometric measurements of the frames of all-sky camera, which was operated at the rate of one frame per second. The pulsations under study are associated with the diffuse aurora. For the event with 7 s period, a phase relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Fraser et al, 1996;Nomura et al, 2012) and in the auroral region (e.g. Roldugin et al, 2013). However, Pc1 pulsations appear also in regions of open geomagnetic field lines, such as cusp/mantle (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fraser et al, 1996;Nomura et al, 2012) and in the auroral region (e.g. Roldugin et al, 2013). However, Pc1 pulsations appear also in regions of open geomagnetic field lines, such as cusp/mantle (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Foat et al [] have found that the frequency of quasi‐periodic modulation (~0.05–0.1 Hz) was observed in the X‐rays flux. Furthermore, all of the X‐rays burst were accompanied by ~0.2 Hz increase in the first mode of SR frequency [ Roldugin et al , ]. This frequency is the same for the polhodic cone ω /2 π (1).…”
Section: Discussionmentioning
confidence: 99%
“…The bipolar, converging or diverging, perpendicular electric fields and U‐shaped potential structures are probably related with the parallel electric fields [ Mozer and Kletzing , ]. The geophysical importance of Pc1 pulsations to the auroral region is their close connection to proton precipitation [ Roldugin et al , ] and traveling convection vortices (TCV) [ Engebretson et al , ]. As a result of upward FAC, the truncated cone appears in the polar aurora region with the Otruez¯ axis acting as an axis of symmetry that is referred to the electron cavity aurora (ECA) and performs in the vertical direction with shear Alfvén waves (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…In general, human beings experience a variety of physiological and medical effects that can be traced to both geophysical and electric power sources. Among these varied geophysical sources one finds Schumann resonances (Fullerkrug, 2005;Galejs, 1965), diurnal geomagnetic rhythms (Chapman, 1918;Liboff, 2014a), Pc1 magnetospheric oscillations (pearls) (Guglielmi and Kangas, 2007;Roldugin et al, 2013;Rusov et al, 2012) and, most notably, solar storm activity (Liboff, 2014b). The daily swing in the geomagnetic intensity is approximately 20-50 nT (Liboff, 2014a), but deviations can be up to ten times greater during periods of increased solar activity.…”
Section: Sources Of Environmental Elf Fieldsmentioning
confidence: 98%